Organoleptic Assessment of Fish-Based Ready-to-Use Supplementary-Food (RUSF) Rich in Essential Fatty Acid for Pregnant Women to Prevent Stunting - Sari Kusuma, Titis; Muslihah, Nurul; Rakhmani, Shinta Kirana; Setiawan, Eunike Cecilia; Fahazria, Fanny Hanifa; Fitrinisa, Wida Rizki (Indonesian Journal of Human Nutrition, 2024)
Stunting is a critical health issue with short- and long-term impacts on health and economic outcomes. Insufficient nutritional intake during pregnancy and early childhood is a key factor contributing to stunting. This study examines the efficacy of fish-based Ready-to-Use Supplementary Food (RUSF) rich in omega-3 fatty acids in preventing stunting by improving maternal nutrition during pregnancy. One of the determining factors is insufficient food intake in quantity and quality during pregnancy and the early stages of introducing complementary foods alongside breastfeeding. Long-chain omega-3 fatty acids (LCPUFAs) have been shown to positively influence health and linear growth for fetuses and children under two years of age. The use of fish-based functional food for pregnant women and children under two years to prevent stunting has not been widely carried out in Indonesia, in terms of the formulation, product types, or efficacy of Ready-to-Use Supplementary Food (RUSF). The stages of the research method were (1) identifying the content of omega-3 fatty acids and heavy metals in lemuru fish, (2) developing RUSF formulations based on snack bars and lemuru fish sausages made from omega-3-standardized raw materials, and (3) conducting acceptance tests of these RUSF products on children aged 6-35 months and pregnant women. This research is expected to develop nutritional supplements in the form of RUSF based on lemuru fish, mackerel, and tuna to serve as functional food products that help pregnant women prevent and control stunting.